Prevalence and antibiotic susceptibility patterns of Shigella and Salmonella among children aged below five years with Diarrhoea attending Nigist Eleni Mohammed memorial hospital, South Ethiopia - Wondwossen Abebe; Alemu Earsido; Solomon Taye; Mesfin Assefa; Adane Eyasu; Girma Godebo (BMC, 2018)
Abstract Background Diarrhoeal disease is the second leading cause of death among children aged below 5 years. Even though, both preventable and treatable diseases, globally there are nearly 1.7 billion cases of childhood diarrhoeal disease and responsible for killing around 525,000 children every year. Shigella and Salmonella species were the leading cause of etiologic agents for diarrhoea associated deaths. The aim of this study was to determine the prevalence and antibiotic susceptibility patterns of Shigella and Salmonella isolated from children aged below 5 years with diarrhoea attending Nigist Eleni Mohammed Memorial Hospital, Hossana, South Ethiopia. Methods A cross sectional study was conducted from June 02 to September 24, 2017. Two hundred four children aged below 5 years with diarrhoea were enrolled consecutively using convenience sampling technique. Stool specimens were processed in accordance with the standard bacteriological methods and antibiotic susceptibility pattern of the isolates was determined using disc diffusion method. Data were analyzed using SPSS version 20. Results Out of the 204 children aged below 5 years with diarrhoeal disease 19/204 (9.3%, [95%CI, 5.7-13.7%]) of them were positive for bacterial growth, of which 17/204(8.3%) were Shigella species and 2/204(1%) were Salmonella species. Both Shigella and Salmonella isolates were 100% susceptible to norfloxacin, nalidixic acid and kanamycin. However, isolates of Shigella showed 100, 76.5 and 64.7% resistance to ampicillin, gentamicin and cotrimoxazole respectively while Salmonella species were highly resistant to ampicillin and gentamicin (100% each). Conclusions Salmonella and Shigella species is prevalent in the current study area. Among the tested antibiotics, norfloxacin, nalidixic acid and kanamycin were found to be most effective for both isolates. Both species are developing resistance to the commonly prescribed antibiotic. Therefore, culture based bacterial species identification and antimicrobial susceptibility testing services are strongly recommended to avoid empirical treatment in the study area.